GENETIC TRANSFORMATION OF CARROT (DAUCAS CAROTA L.) TO EXPRESS HEPATITIS B SURFACE ANTIGEN GENE FOR EDIBLE VACCINE OF HBV - S. Ilyas; N. Asghar; N. Munir; M. Aftab; S. Naz1 (Journal of Animal and Plant Sciences, 2020)
Pakistan is considered as endemic to hepatitis viruses, particularly hepatitis B virus (HBV). Though vaccine against HBV is available but is still spreading in developing countries because of the various socioeconomic conditions. Therefore developing of edible vaccine is a good approach to target the spread and control of such deadliest viruses particularly in developing countries. Various fruits or vegetables can be used for production of edible vaccine. Here we are using carrot as it is much economical as compared to many fruits with greater shelf life and can be consumed without any processing. The current study was done after realizing the high transformation rates centered on strain and cultivar selection reporting a highly efficient protocol to transform carrot seedling exploiting direct somatic embryogenesis of carrot to give high transient expression of protein. In vitro grown disease-free healthy carrot plants were employed and transferred to MS medium with 1 mg/l BAP and 0.5 mg/l 2, 4- D. The surface antigen S gene of Hepatitis B Virus, a potential antigen for production of antibodies by the immune system was acquired from native genotype of HBV and cloned in vector pCAMBIA 1301. This construct was introduced into Agrobacterium tumefaciens and transformed to local carrot cultivars. The transformation efficiency of HBsAg gene was upto 52 % in one carrot cultivar that proved to be highest values reported till date. Hence, carrot cultivar offers promising prospects for production of economically viable and efficient anti-HBV vaccine. This study laid the basis for the development of a novel edible vaccine for hepatitis B in Pakistan that could be administered orally and especially in carrot which is essential vegetable crop grown widely.
Keywords: Agrobacterium-mediated transformation; Hepatitis B surface antigen; Daucus carota; Edible vaccine; Somatic embryogenesis